2016
DOI: 10.1155/2016/6962574
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Newer Antidiabetic Medications for Ramadan Fasting Diabetic Patients

Abstract: Hypoglycemia is the most common side effects for most glucose-lowering therapies. It constitutes a serious risk that faces diabetic patients who fast during Ramadan (the 9th month in the Islamic calendar). New glucose-lowering classes like dipeptidyl peptidase-4 (DPP-4) inhibitors, glucagon-like peptide 1 receptor agonist (GLP-1 RA), and sodium-glucose cotransporter-2 (SGLT-2) inhibitors are efficacious in controlling blood glucose level with less tendency to induce hypoglycemia and thus may constitute a good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…There is scarce data on the rate of hypoglycaemia in non-insulin-treated patients with type 2 diabetes during Ramadan fasting. However, recent studies have shown that the newer anti-diabetic medications – DPP-4 inhibitors, GLP-1 agonists, and SGLT2 inhibitors – are safe during Ramadan fasting and have lower risk for hypoglycaemia compared to SU [12,14,18,19]. Pre-Ramadan individualized advice and education provided at our centre may have played a role in preventing significant increase in the rate of hypoglycaemia [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…There is scarce data on the rate of hypoglycaemia in non-insulin-treated patients with type 2 diabetes during Ramadan fasting. However, recent studies have shown that the newer anti-diabetic medications – DPP-4 inhibitors, GLP-1 agonists, and SGLT2 inhibitors – are safe during Ramadan fasting and have lower risk for hypoglycaemia compared to SU [12,14,18,19]. Pre-Ramadan individualized advice and education provided at our centre may have played a role in preventing significant increase in the rate of hypoglycaemia [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…This can be caution in fasting, because of extreme temperatures in Pakistan, especially in summers. 3 In previous literature, EPIDIAR study 4 showed that there was a 7.5% increased risk of hypoglycemia in patients who wanted to fast. It showed the importance of hypoglycemia as the single most important complication of fasting diabetics.…”
Section: Introductionmentioning
confidence: 97%
“…Fasting is one of the basic principles of Islam, a religion that over a billion people practice. Healthy Muslim adults must cease eating and drinking from sunrise to sunset during Ramadan, the 9 th lunar month in the Islamic calendar [1,2]. Presently, there are more than 150 million Muslim diabetics globally [3], and the number of diabetics worldwide is expected to surpass 360 million by 2030 [2].…”
Section: Introductionmentioning
confidence: 99%